2003
DOI: 10.1124/jpet.103.051615
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolar Solution Effects in Guinea Pig Airways. II. Epithelial Bioelectric Responses to Relative Changes in Osmolarity

Abstract: Osmotic challenge of airways alters the bioelectric properties of the airway epithelium and induces the release of factors that modulate smooth muscle tone. Recent studies in our laboratory suggested that methacholine-contracted airways relax in response to incremental increases in osmolarity, rather than from cell shrinkage or absolute solute concentration. In the present study, guinea pig tracheae were mounted in Ussing chambers to elucidate the bioelectric effects of challenge of the epithelium with hyperos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Previous experiments have suggested Wu et al, 2003) that EpDRF is released in response to incremental changes in osmolarity as opposed to absolute osmolarity of solutions bathing the epithelium. Furthermore, the release of EpDRF is associated with changes in bioelectric activity of the epithelium (Dortch-Carnes et al, 1999;Wu et al, 2003). In the present study, a panel of agents were examined for their effects on relaxation responses to hyperosmolar solution, to gain insight into the identity of EpDRF.…”
Section: Ethenyl]phenyl][[3-(dimethylamino)-3-oxopropyl]thio]methyl]tmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous experiments have suggested Wu et al, 2003) that EpDRF is released in response to incremental changes in osmolarity as opposed to absolute osmolarity of solutions bathing the epithelium. Furthermore, the release of EpDRF is associated with changes in bioelectric activity of the epithelium (Dortch-Carnes et al, 1999;Wu et al, 2003). In the present study, a panel of agents were examined for their effects on relaxation responses to hyperosmolar solution, to gain insight into the identity of EpDRF.…”
Section: Ethenyl]phenyl][[3-(dimethylamino)-3-oxopropyl]thio]methyl]tmentioning
confidence: 98%
“…Mention of brand name does not constitute product endorsement. This article is the third one of a series of four companion articles that report the effects of hyperosmolar solutions in guinea pig airways Wu et al, 2003 1999; , although an inhibitory effect of hemoglobin but not of methylene blue or inhibitors of nitricoxide synthase suggested that EpDRF release by hyperosmolar solution has features resembling nitric oxide (Munakata et al, 1990;Fedan et al, 1999). It is not known whether the EpDRF released by contractile agonists in the coaxial bioassay preparation, and that released by hyperosmolar solution in the perfused trachea, are the same substance.…”
Section: Ethenyl]phenyl][[3-(dimethylamino)-3-oxopropyl]thio]methyl]tmentioning
confidence: 99%
See 2 more Smart Citations
“…Mention of brand name does not constitute product endorsement. This article is the fourth one of a series of four companion articles that report the effects of hyperosmolar solutions in guinea pig airways (Fedan et al, 2003a,b;Wu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%